2001
DOI: 10.1071/ar00115
|View full text |Cite
|
Sign up to set email alerts
|

Yield performance and adaptation of some Australian and CIMMYT/ICARDA developed wheat genotypes in the West Asia North Africa (WANA) region

Abstract: A set of 29 advanced breeding lines and named cultivars from different breeding programs in Australia was compared with 18 genotypes developed by the CIMMYT/ICARDA breeding programs for their adaptation and yield performance using 5 locations in the WANA region for 2 years. Classification analysis identified 13 CIMMYT/ICARDA genotypes that had a pattern in yield performance similar to 2 Australian cultivars, Leichhardt and Hartog. The classification of environments effectively identified trials that experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Nevertheless, the yield progress observed with the introduction of CIMMYT cultivars under all environmental conditions (even when nitrogen level was moderate, lodging was not severe and no pest or disease epidemic occurred) indicates the wide adaptability of these cultivars, as is also suggested by Ortiz-Monasterio et al (1997) and Trethowan et al (2002). Sivapalan et al (2001) also observed a wider adaptation capacity for CIMMYT/ICARDA-developed bread wheat genotypes compared with Australian genotypes in the WANA region.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, the yield progress observed with the introduction of CIMMYT cultivars under all environmental conditions (even when nitrogen level was moderate, lodging was not severe and no pest or disease epidemic occurred) indicates the wide adaptability of these cultivars, as is also suggested by Ortiz-Monasterio et al (1997) and Trethowan et al (2002). Sivapalan et al (2001) also observed a wider adaptation capacity for CIMMYT/ICARDA-developed bread wheat genotypes compared with Australian genotypes in the WANA region.…”
Section: Discussionmentioning
confidence: 56%
“…The impact of abiotic stresses on response patterns in genotypes across diff erent environments has been reported in studies in Australia (Cooper et al, 1994), West Africa-North Asia (Sivapalan et al, 2001), and in winter yield trials in Ontario, Canada . The impact of abiotic stresses on response patterns in genotypes across diff erent environments has been reported in studies in Australia (Cooper et al, 1994), West Africa-North Asia (Sivapalan et al, 2001), and in winter yield trials in Ontario, Canada .…”
Section: Discussionmentioning
confidence: 93%
“…In this study, a hierarchical cluster analysis based on G × L interaction of AUDPC for spot blotch appeared to be eff ective for subdividing the diverse South Asian region into more uniform subregions for better germplasm evaluation. The impact of abiotic stresses on response patterns in genotypes across diff erent environments has been reported in studies in Australia (Cooper et al, 1994), West Africa-North Asia (Sivapalan et al, 2001), and in winter yield trials in Ontario, Canada . If wide adaptability is the main breeding objective, representative locations from the eastern Indo-Gangetic plains of India and Nepal (Cluster I) should be chosen.…”
Section: Discussionmentioning
confidence: 93%
“…The parental lines contrast for yield and stay-green. SeriM82 is a high-yielding drought-tolerant, stay-green line ( Sivapalan et al , 2000 , 2001 ; Olivares-Villegas et al , 2007 ), while Hartog is a senescent cultivar adapted to subtropical Australia ( Manschadi et al , 2006 , 2010 ; Christopher et al , 2008 ).…”
Section: Methodsmentioning
confidence: 99%